Chinese herbal medicine and its active compounds in attenuating renal injury via regulating autophagy in diabetic kidney disease - Liu, Peng; Zhu, Wenhui; Wang, Yang; Ma, Guijie; Zhao, Hailing; Li, Ping (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD) is the main cause of end-stage renal disease worldwide, and there is a lack of effective treatment strategies. Autophagy is a highly conserved lysosomal degradation process that maintains homeostasis and energy balance by removing protein aggregates and damaged organelles. Increasing evidence suggests that dysregulated autophagy may contribute to glomerular and tubulointerstitial lesions in the kidney under diabetic conditions. Emerging studies have shown that Chinese herbal medicine and its active compounds may ameliorate diabetic kidney injury by regulating autophagy. In this review, we summarize that dysregulation or insufficiency of autophagy in renal cells, including podocytes, glomerular mesangial cells, and proximal tubular epithelial cells, is a key mechanism for the development of DKD, and focus on the protective effects of Chinese herbal medicine and its active compounds. Moreover, we systematically reviewed the mechanism of autophagy in DKD regulated by Chinese herb compound preparations, single herb and active compounds, so as to provide new drug candidates for clinical treatment of DKD. Finally, we also reviewed the candidate targets of Chinese herbal medicine regulating autophagy for DKD. Therefore, further research on Chinese herbal medicine with autophagy regulation and their targets is of great significance for the realization of new targeted therapies for DKD.